The dynamics of governance and sustainable development goals in the Global South - Liu, Hong (2022)
This special issue on ‘The Dynamics of Governance and Sustainable Development Goals in the Global South’, with a focus on the ‘Asian Models of Governance’, aims to fill the gap by contributing to expanding and advancing the transnational knowledge transfer literature by bringing new cases from the Global South. It also hopes to further advance the discussions translating some aspects of Asian experiences of governance in developing an outcome-driven knowledge and policy transfer model for SDGs. The articles in this issue of Global Policy were selected from papers first presented at the London School of Economics – IDEAS and Nanyang Technological University – Nanyang Centre for Public Administration (LSE-IDEAS and NTU-NCPA) Joint Workshop on the Dynamics of Knowledge Transfer and Governance in the Global South, held at the London School of Economics in November 2019.